2018
DOI: 10.1111/jce.13685
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical relevance of ablation to the pulmonary artery root: Clinical implications for characterizing the pulmonary sinus of Valsalva and coronary artery

Abstract: Both the left and RASs are intimately related to the aortic root. The LAS is more often close to LMCA, LAD, and the LASV. The anterior sinus is more frequently related to LAD than LMCA. This information may help heighten operator awareness of safety for increasingly performed complex procedures in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In our clinical experience, such intracardiac echocardiography allows real time assessment of the relationship between the pulmonary valvar sinuses and the coronary arteries. In this regard, this study by Dong et al clearly shows how an ablation catheter that is wedged tightly within the left adjacent pulmonary valvar sinus can be in close proximity to the main stem of the left coronary artery and the proximal segment of the left anterior descending artery. With a catheter in this location, it is certainly possible to injure the coronary arteries, especially when using high contact force with irrigated ablation.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…In our clinical experience, such intracardiac echocardiography allows real time assessment of the relationship between the pulmonary valvar sinuses and the coronary arteries. In this regard, this study by Dong et al clearly shows how an ablation catheter that is wedged tightly within the left adjacent pulmonary valvar sinus can be in close proximity to the main stem of the left coronary artery and the proximal segment of the left anterior descending artery. With a catheter in this location, it is certainly possible to injure the coronary arteries, especially when using high contact force with irrigated ablation.…”
mentioning
confidence: 84%
“…The processes of dissection required to reveal these relationships are likely to introduce errors when attempts are made to take measurements between anatomic landmarks. As Dong et al show, these features can be demonstrated with exquisite accuracy using virtual dissection of computed tomographic datasets, with the measurements made with comparable accuracy and the illustrations being self‐explanatory. It should be also noted that the authors distinguish clearly between the valvar sinuses and the leaflets that they support.…”
mentioning
confidence: 96%
See 3 more Smart Citations